The Influence of Perceived Value and Quality on Tourist Loyalty in Sharia Tourism with Satisfaction Mediation - Melani, Meisy (JURNAL EKONOMI SYARIAH, 2025)
This study aims to analyze the influence of perceived value and perceived quality on tourist loyalty, with tourist satisfaction as a mediating variable, at the Torang Sari Bulan sharia tourism destination in Lima Puluh Kota Regency. The phenomenon of declining tourist visits in recent years has created a need to evaluate tourists' perceptions of the value and quality of the destination, as well as their satisfaction. This study employs a quantitative approach using a survey method on 385 respondents who are tourists at Torang Sari Bulan. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) via the SmartPLS software. The results indicate that perceived value and perceived quality significantly influence tourist satisfaction, and tourist satisfaction positively influences tourist loyalty. Additionally, tourist satisfaction was found to be a significant mediator between perceived value and perceived quality on tourist loyalty. These findings reinforce the theoretical model stating that perceptions of value and quality will drive tourist loyalty when accompanied by high levels of satisfaction. Therefore, managers of Islamic tourism destinations are advised to continue improving perceptions of value and service quality, as well as paying attention to tourist satisfaction in every aspect of service delivery.